2015
DOI: 10.21168/rbrh.v20n3.p708-721
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos fatores intervenientes no processo de salinização em reservatórios superficiais do semiárido brasileiro

Abstract: Os açudes representam a principal fonte de água para suprir as demandas no semiárido do nordeste brasileiro. A presença da água não significa garantia de abastecimento, uma vez que, além da intermitência dos rios, o aporte de sais e esgotos na água torna-a comprometida para o consumo humano, animal e para a irrigação. Neste contexto, a presente pesquisa avaliou o processo de salinização das águas superficiais de cinco reservatórios com características distintas da bacia hidrográfica do rio Jacuípe, uma área de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Water salinization is a recurring problem in Northeastern Brazil, as the region's climatic conditions contribute significantly to the salinization processes. The literature (Santos et al, 2000;Souza Filho & Campos, 2002;Meireles et al, 2007;Palácio et al, 2011;Fontes et al, 2015) has highlighted the following as potential factors for surface water salinization: (i) atmospheric deposition of marine aerosol, (ii) high salt concentration surface water influx; (iii) excessive evaporation rates (about 2000 mm/year), (iv) aquifers with high saline concentration that can reach surface waters and (v) no accumulated reservoir water renewal for long periods of time. Santos et al (2000) evaluated reservoirs located in the southwest of Bahia, the relationship between the water retention time and the age of the reservoir with salinization.…”
Section: Introductionmentioning
confidence: 99%
“…Water salinization is a recurring problem in Northeastern Brazil, as the region's climatic conditions contribute significantly to the salinization processes. The literature (Santos et al, 2000;Souza Filho & Campos, 2002;Meireles et al, 2007;Palácio et al, 2011;Fontes et al, 2015) has highlighted the following as potential factors for surface water salinization: (i) atmospheric deposition of marine aerosol, (ii) high salt concentration surface water influx; (iii) excessive evaporation rates (about 2000 mm/year), (iv) aquifers with high saline concentration that can reach surface waters and (v) no accumulated reservoir water renewal for long periods of time. Santos et al (2000) evaluated reservoirs located in the southwest of Bahia, the relationship between the water retention time and the age of the reservoir with salinization.…”
Section: Introductionmentioning
confidence: 99%
“…They still reported that the set of local changes associated with salinization occur, mainly due to human interference, and when combined with natural events, such as prolonged drought, contribute to the intensification of this process. In addition to this event, other factors of a natural order that have been identified as potential sources of the salinization process of a watershed may be cited, such as atmospheric deposition of marine aerosols, salts from the dissolution of soil and rocks (FONTES et al, 2015), characteristics of climate variability, with concentrated and heavy rains and high evaporation rates (MEDEIROS et al 2014).…”
Section: Resultados E Discussão Entrevistasmentioning
confidence: 99%
“…Os entrevistados acrescentaram que as mudanças locais associadas à salinização em sua maioria ocorreram devido à interferência humana, o que combinado aos eventos naturais, como estiagem prolongada, contribuem para intensificação deste processo. Além desse evento, outros fatores de ordem natural que têm sido apontados como fontes potenciais do processo de salinização de uma bacia hidrográfica incluem: a deposição atmosférica de aerossóis marinhos, sais provenientes da dissolução do solo e rochas (FONTES et al, 2015), características de variabilidade climática, com chuvas concentradas e de forte intensidade e altas taxas de evaporação (MEDEIROS et al 2014).…”
Section: Resultados E Discussão Entrevistasunclassified
“…A salinização de reservatórios é um problema recorrente no Nordeste brasileiro, principalmente na região semiárida onde a taxa de evaporação é em torno de 2000 mm/ano [17,19,[52][53][54]. De acordo com Santos et al (2000) [19] a salinização tem aumentado com a idade dos reservatórios ou com o tempo de retenção hidráulica e por isso, uma estratégia possível para diminuir a velocidade do aumento da salinização, seria a renovação das águas acumuladas pelo controle das vazões defluentes.…”
Section: Mecanismos Que Controlam a Química Da áGuaunclassified